Biomechanical analysis of curb ascent in persons with Ertl and non-Ertl transtibial amputations. (February 2020) - Ferris, Abbie E; Christiansen, Cory L; Heise, Gary D; Hahn, David; Smith, Jeremy D
Background: Persons with transtibial amputation report curb negotiation is more challenging than negotiating stairs. It is unknown if amputation technique influences curb negotiation ability. Traditional transtibial amputation surgical techniques do not join the distal tibia and fibula (non-Ertl), whereas a transtibial osteomyoplastic amputation (Ertl) creates a "bone bridge" connection. The Ertl may facilitate ambulation through greater residual end load bearing. Objectives: To determine if ability to negotiate a curb differs between Ertl and non-Ertl groups. Study design: Cross-sectional study. Methods: Non-Ertl ( n  = 7) and Ertl ( n  = 5) participants ascended a 16-cm curb using their amputated and intact limb as the lead limb. Motion data and ground reaction forces were used to calculate ankle, knee, hip, and total limb work for ground and curb steps. Results: On the ground, the amputated limb of both groups produced less work than the intact limb. In contrast, on the curb step, the Ertl amputated limb generated more net hip work than the non-Ertl amputated limb. As a result, the net limb work of the Ertl amputated limb did not differ from the non-amputated limbs. Conclusion: Comparisons between the amputated limb of Ertl and non-Ertl groups suggest use of a different curb stepping pattern between groups. Clinical relevance: These findings suggest that surgical technique may influence curb negotiation ability in individuals with transtibial amputation. Specifically, the Ertl group is able to produce more hip power than the non-Ertl group while negotiation a curb which may be attributed to the increased ability to end-load bear on the residual limb.